Effect of Cu doping in ZnO nanoparticles for increased voltage generation, storage capacity, and energy conversion efficiency in photoelectrochemical cell. Issue 13 (2nd July 2016) - Bandyopadhyay, Poonam; Dey, Anindita; Basu, Ruma; Nandy, Papiya; Das, Sukhen
ABSTRACT: The synthesis, characterization, and application of engineered nanomaterials in different fields have opened up new aspects of nanotechnology. Using a simple chemical method, this study describes the synthesis of highly dispersed Cu-doped ZnO nanoparticles with different concentrations of Cu (1, 3, and 5 mM). The nanoparticles thus synthesized were tested for their effect on photo-induced voltage generation, enhancement of storage capacity, and energy conversion efficiency in hybrid photoelectrochemical (PEC) cell. Maximum photovoltage ( 680 mV) with highest storage capacity ( 53 h) and high energy conversion efficiency ( 2.16%) was generated using these nanoparticles when the doping concentration of Cu was 3 mM.